A new approximate solution for the Telegraph equation of space-fractional order derivative by using Sumudu method - AL-Safi, Mohammed G. S.; AL-Hussein, Wurood R. Abd; Al-Shammari, Ayad Ghazi Naser (Iraqi Journal of Science, 2018)
In this work, we are concerned with how to find an explicit approximate solution (AS) for the telegraph equation of space-fractional order (TESFO) using Sumudu transform method (STM). In this method, the space-fractional order derivatives are defined in the Caputo idea. The Sumudu method (SM) is established to be reliable and accurate. Three examples are discussed to check the applicability and the simplicity of this method. Finally, the Numerical results are tabulated and displayed graphically whenever possible to make comparisons between the AS and exact solution (ES).